THE INFLUENCE OF OWNERSHIP STRUCTURE, FREE CASH FLOW, AND COMPANY GROWTH ON DIVIDEND POLICY: (Case Study of LQ 45 Companies Listed on BEI in 2017-2021) - Median Kristianti Harefa; Desi Jelanti (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
Dividend policy is a critical decision concerning the distribution of company profits, determining how much profit will be distributed as dividends and how much will be retained as retained earnings. Therefore, companies must carefully consider these factors when making decisions regarding their dividend policy. This study aims to examine the influence of Ownership Structure, Free Cash Flow, and Company Growth on Dividend Policy. The subjects of this research are companies included in the LQ 45 index listed on the Indonesia Stock Exchange for the period of 2017-2021. The methodology used is regression analysis using Panel Data, and the sampling technique employed is purposive sampling. Based on the test results, it is found that the variables Managerial Ownership Structure and Company Growth have a positive and significant impact on Dividend Policy, affecting decisions made by companies for the welfare of shareholders. On the other hand, Free Cash Flow shows a negative and insignificant effect on Dividend Policy, indicating that the greater the free cash flow, the smaller the dividend shared by the company.